Effects of Green Mussel Shells (Perna viridis) and Chitosan Extracted from Milkfish (Chanos chanos) Scales on the Compressive Strength of Mortar and Concrete - Bernardo Lejano; Kenneth Jae Elevado; Lorenzo Martin Chua; Simon Rohi Cuartero; Vince Philip Fabian; Alyanna Ysabel Rase (Resources)
It is estimated that in the construction industry, cement production contributes to 7% of global CO2 emissions. Because of this, alternative materials, including biological resources and wastes, are being explored to determine their viability as substitutes for conventional concrete aggregates. This study investigates the feasibility of using green mussel shells (GMSs) as a partial cement replacement and chitosan derived from milkfish scales as an additive in concrete. Addressing environmental concerns tied to cement production, the research evaluates the potential of GMSs and chitosan to enhance mortar and concrete properties. This study was conducted in two phases: phase one focused on mortar with varying percentages of GMSs (0%, 5%, 10%, 15%, and 20%) and chitosan (0%, 0.25%, 0.50%, 0.75%, and 1%), while phase two applied the phase one results that resulted in the highest compressive strength of concrete. The results indicate that 10% GMS and 0.25% chitosan improved mortar strength by 38.74%, although high GMS levels reduced workability. In concrete, 10% GMS without chitosan decreased compressive strength by up to 47% due to magnesium impurities in GMSs, verified by FTIR analysis. This study highlights GMSs’ and chitosan’s potential but emphasizes impurity management for its application feasibility.